Development of a method for protonema proliferation of peat moss (Sphagnum squarrosum) through regeneration analysis. Issue 2 (26th August 2018) - Zhao, Wenqian; Li, Zeling; Hu, Yongyue; Wang, Min; Zheng, Shirui; Li, Qiuping; Wang, Youfang; Xu, Lin; Li, Xiaofang; Zhu, Ruiliang; Reski, Ralf; Sun, Yue
Summary: The moss Sphagnum (peat moss) is ecologically and economically important. There is a paucity of physiological and developmental studies on Sphagnum because of the lack of an axenic culture system for its whole life cycle. A culture system has been established for the Sphagnum gametophore, but not the protonema (juvenile vegetative stage after spore germination). Therefore, the aim of this study was to develop a protonema culture system for Sphagnum. Sphagnum squarrosum gametophore tissue was disrupted and then cultured in liquid Knop medium. The regeneration of protonemata from the gametophore fragments was analyzed in detail by microscopy. We observed a developmental balance between filamentous and thalloid protonemata, and growth competition between the thalloid protonema and the gametophore. On the basis of these findings, we established a relatively stable peat moss protonema proliferation method. Using this method, all the developmental stages of peat moss vegetative growth could be obtained through differentiation or regeneration. The method can provide abundant homogeneous Sphagnum materials at desired stages for physiological and developmental studies, and will be useful for large‐scale Sphagnum vegetative proliferation. The regeneration analysis method will be useful for establishing protonema proliferation systems for other mosses.